Sleep quality and its association with menopausal and climacteric symptoms - Mariana Alvina dos Santos; Aline Nascimento Vilerá; Anneliese Domingues Wysocki; Flávia Helena Pereira; Deíse Moura de Oliveira; Vinícius Batista Santos
ABSTRACT Objective: to assess sleep quality in menopausal women and its association with symptoms related to this period. Method: this is a cross-sectional, analytical and correlational study. Sleep was assessed using the Pittsburgh Sleep Quality Index; and climacteric symptoms, according to the Menopause Rating Scale. To compare the total score and each Menopause Rating Scale domain with the PSQI classification, the Mann-Whitney U non-parametric test was used. P<0.05 was considered significant. Results: 261 women (67.8%) were classified as bad sleepers. There was a positive and significant correlation between the sleep scale scores and the total menopause score and its domains. Women categorized as poor sleepers had worse scores on the menopause symptom scale. Conclusion: women with worse sleep quality revealed greater severity of symptoms related to menopause.